Determinants of Health Service Quality in Health Service Institutions in The Era of The Regional Public Service Agency (BLUD): Systematic Literature Review - Siti Aisyah Nuraeni; Aden Aulia Rahman; Gugum Ahmad Suandana; Cepi Hermansyah; Rosa Eka Putri (Siber Nusantara Research, 2026)
The quality of health services is an important indicator in assessing the success of health services in health service institutions in the era of the Regional Public Service Agency (BLUD). This study aims to analyze the determinants of health service quality through the Systematic Literature Review (SLR) approach of the PRISMA method. Articles were searched on Google Scholar, PubMed, ScienceDirect, and Garuda databases with a publication range of 2020–2025 using keywords related to health service quality and BLUD. The results of the identification obtained 1,377 articles, then a screening and selection process was carried out until 10 articles were analyzed. The results of the study show that the main determinants of health service quality include the implementation of BLUD, the competence of health human resources, infrastructure, administrative systems, service digitization, and patient satisfaction. The competence of health workers is the most dominant factor in improving the quality of services. This study concludes that improving the quality of health services requires strengthening management, human resources, service facilities, and technology-based service systems.